Impact of 2014 Japanese practice guidelines on treatment patterns in patients with myasthenia gravis: an insurance claims database study - Akiyuki Uzawa; Shingo Konno; Makoto Samukawa; Izumi Mishiro; Hiroshi Todaka; Kentaro Taki; Céline Quelen; Adrianna Czubin; Renata Majewska; Kunihiko Shiraiwa; Yohei Ohashi (BMJ Open, 2025)
Objectives To evaluate changes in oral corticosteroid (OCS) use after the publication of the 2014 Japanese clinical practice guidelines for myasthenia gravis (MG).Design Retrospective cohort study performed in three Japanese health insurance databases: the JMDC database between 2005 and 2021; the DeSC database covering the National Health Insurance (NHI) and the DeSC database covering the Late-Stage Elderly Healthcare Service (LSEHS) between 2014 and 2021. Achievement of OCS ≤5 mg/day was defined as ≥90 days of consecutive OCS ≤5 mg/day during follow-up, without any gap longer than 60 days between two consecutive claims. The time to achieve OCS ≤5 mg/day was estimated using Kaplan-Meier survival analysis.Setting Real-world treatment setting in Japan.Participants Patients aged ≥16 years with a record of MG (International Classification of Diseases 10th edition code: G70.0) with a serological test, who had baseline period ≥180 days before inclusion with no MG claim and who started immunotherapy (including OCS) within 90 days of MG diagnosis.Outcome measures Prescription of OCS and other therapies for MG.Results Overall, 811 patients were included. The mean age was 49 years in the JMDC, 61 years in the NHI and 80 years in the LSEHS. In the JMDC, the median time to achieve OCS ≤5 mg/day was significantly shorter (p=0.042; log-rank test) in patients included in 2015 or later (11.0 months) than in patients included before 2015 (17.9 months). The median time to achieve OCS ≤5 mg/day was shorter in the LSEHS (6.5 months) than in the JMDC (11.0 months) and the NHI (11.7 months).Conclusions Faster tapering of the OCS dose was observed in patients starting treatment after the publication of the 2014 guidelines, although use of higher-dose OCS remained widespread after this date. This highlights the need to improve awareness of guidelines by healthcare providers in order to decrease the burden of higher-dose OCS.Trial registration number Clinical Trials Registry (UMIN-CTR): UMIN000051155; Post-results.